Let's denote the expression "x-2y=\\zeta (x,y)" and "3x+y=\\xi(x,y)". Then rewrite task as
(1) "Z(x,y)=f(\\zeta(x,y))+g(\\xi(x,y))"
The first derivatives by the rule of differentiation of nested functions will be
(2) "Z'_x=f'_{\\zeta}\\cdot \\zeta'_x+g'_{\\xi}\\cdot \\xi'_x=f'_{\\zeta}+3g'_{\\xi}"
(3) "Z'_y=f'_{\\zeta}\\cdot \\zeta'_y+g'_{\\xi}\\cdot \\xi'_y=-2f'_{\\zeta}+g'_{\\xi}"
The second derivatives are
(4) "Z''_{xx}=f''_{\\zeta\\zeta}\\cdot \\zeta'_x+3g''_{\\xi\\xi}\\cdot \\xi'_x=f''_{\\zeta\\zeta}+9g''_{\\xi\\xi}"
(5) "Z''_{xy}=f''_{\\zeta\\zeta}\\cdot \\zeta'_y+3g''_{\\xi\\xi}\\cdot \\xi'_y=-2f''_{\\zeta\\zeta}+3g''_{\\xi\\xi}"
(6) "Z''_{yy}=-2f''_{\\zeta\\zeta}\\cdot \\zeta'_y+g''_{\\xi\\xi}\\cdot \\xi'_y=4f''_{\\zeta\\zeta}+g''_{\\xi\\xi}"
Let's substitute these expressions into the equation of the problem and give similar terms.
(7) "Z''_{xx}+AZ''_{xy}+BZ''_{yy}=0\\\\f''_{\\zeta\\zeta}+9g''_{\\xi\\xi}+A\\cdot (-2f''_{\\zeta\\zeta}+3g''_{\\xi\\xi})+B\\cdot(4f''_{\\zeta\\zeta}+g''_{\\xi\\xi})=0"
(8) "f''_{\\zeta\\zeta}\\cdot (1-2A+4B)+g''_{\\xi\\xi}\\cdot(9+3A+B)=0"
Equation (8) can be performed for any "f" and "g" only if the expressions in parentheses are both 0. We get a system of two algebraic equations with two unknowns.
(9) "\\begin{cases}\n 1-2A+4B=0 \\\\\n 9+3A+B=0\n\\end{cases}"
In standard form they are
(10) "\\begin{cases}\n 2A-4B=1 \\\\\n 3A+B=-9\n\\end{cases}"
The solution to this system is easy to find "A=-\\frac{35}{14}; B=-\\frac{21}{14}" or "A=-\\frac{5}{2}; B=-\\frac{3}{2}"
Answer: "A=-\\frac{5}{2}; B=-\\frac{3}{2}"
Comments
Leave a comment